2021
DOI: 10.32699/spektra.v7i2.216
|View full text |Cite
|
Sign up to set email alerts
|

Spektrum Cahaya Sebagai Alternatif Media Pembelajaran Praktikum Fisika

Abstract: Spectrometer merupakan instrument yang digunakan untuk mengamati dan mengukur sudut deviasi cahaya datang yang dikarenakan pembiasan dan dispersi oleh medium. Spectrometer pada umumnya berfungsi untuk menganalisis cahaya yang datang dari sumber cahaya dengan menggunakan kisi difraksi dalam proses penggunaan nya. Penelitian ini merupakan penelitian pengembangan dengan metode eksperimen. Teknik analisis data yang digunakan adalah deskriptif analisis kuantitatif dengan membandingkan hasil analisis alat dengan per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
0
0
1
Order By: Relevance
“…So it requires the right approach to obtain maximum learning outcomes. This is supported by previous research which revealed misconceptions about the material of the human respiratory system, including research by (Dewi & Purnomo, 2021) which revealed that the percentage of students' answers to the material on the human respiratory system was 62.15%, who experienced misconceptions about the concept of structure and function of the human respiratory organs, respiratory mechanisms, respiratory frequency, respiratory volume and diseases or disorders of the human respiratory system in class VIII students from two classes at SMP Negeri 1 Sidoarjo. Factors that cause misconceptions include the students themselves, learning methods, ways of teaching and context.…”
Section: Introductionsupporting
confidence: 80%
“…So it requires the right approach to obtain maximum learning outcomes. This is supported by previous research which revealed misconceptions about the material of the human respiratory system, including research by (Dewi & Purnomo, 2021) which revealed that the percentage of students' answers to the material on the human respiratory system was 62.15%, who experienced misconceptions about the concept of structure and function of the human respiratory organs, respiratory mechanisms, respiratory frequency, respiratory volume and diseases or disorders of the human respiratory system in class VIII students from two classes at SMP Negeri 1 Sidoarjo. Factors that cause misconceptions include the students themselves, learning methods, ways of teaching and context.…”
Section: Introductionsupporting
confidence: 80%
“…Panjang gelombang dan kecepatan gelombang cahaya kemudian dapat diukur. (dewi, Hasanah, and Adi, 2021).…”
Section: B Spektrometerunclassified